Piece of news of a manuscript of the Historia compendiada del Reino de Navarra, by José Yanguas y Miranda - Panizo Santos, Ignacio (Huarte de San Juan. Geografía e Historia, 2017)
The author communicates the existence of the manuscript entitled Historia compendiada del Reino de Navarra, preserved in the National Historical Archive. It is the original that its author, José Yanguas y Miranda, had to present to the Council of Castile to obtain the printing license in 1832.
Keywords: José Yanguas y Miranda; historiography; Navarre; history of printing